Purinergic Regulation of Respiratory Diseases - Picher, Maryse; Boucher, Richard C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
We proudly present the first book to integrate all aspects of purinergic signaling in the respiratory system. The first chapters introduce basic notions of purinergic pharmacology and metabolism, which allows readers from all scientific backgrounds to fully grasp the importance of these signaling networks for airway defenses, including mucociliary clearance and inflammatory responses. Then, chapters are devoted to the groundbreaking discovery that chronic respiratory diseases, including asthma, cystic fibrosis and chronic obstructive pulmonary disease (COPD), present specific aberrances in purinergic signaling which essentially drive lung complications. The last chapters describe the animal models used to investigate purinergic signaling in respiratory diseases, and the therapeutic applications developed by the pharmaceutical industry based on receptor agonists/antagonists and metabolic correctors. This highly comprehensive manuscript constitutes an invaluable tool for beginners and experts to follow the rapidly evolving research field of purinergic signaling. Furthermore, the critical analysis of past clinical protocols should facilitate the identification of potent therapeutic targets, and provide a better understanding of the data acquired in current clinical trials.
Dedication. Preface -- Chapter 1. Nucleotide Release by Airway Epithelia -- Chapter 2. Mechanisms Regulating Airway Nucleotides -- Chapter 3. Computational Model for the Regulation of Extracellular ATP and Adenosine in Airway Epithelia -- Chapter 4. Regulation of Airway Nucleotides in Chronic Lung Diseases -- Chapter 5. Nucleotide-Mediated Airway Clearance -- Chapter 6. Purinergic Signaling in Wound Healing and Airway Remodeling -- Chapter 7. Purinergic Regulation of Airway Inflammation -- Chapter 8. Animal Models of Airway Diseases -- Chapter 9. Therapeutic Applications. Index.
Keywords: Medicine; Pharmaceutical technology; Emerging infectious diseases; Metabolic diseases; Pneumology; Trauma; Biomedicine; Biomedicine general; Pneumology/Respiratory System; Pharmaceutical Sciences/Technology.; Metabolic Diseases; Infectious Diseases; Traumatic Surgery